Unintentional Monotherapy in Rheumatoid Arthritis Patients Receiving Tofacitinib and Drug Survival Rate of Tofacitinib - Inanc, Nevsun; Abacar, Kerem Y.; Ozturk, Mehmet A.; Tufan, Abdurrahman; Karadeniz, Hazan; Sari, Ismail; Onen, Fatos (Lippincott Williams & Wilkins, 2023)
ObjectiveTo determine the rate of unintentional monotherapy (UM; switching to monotherapy from combination therapy of patients' own volition) in rheumatoid arthritis patients receiving tofacitinib and to evaluate tofacitinib survival rate.MethodsThis national, multicenter study included patients' data from the TURKBIO Registry. Demographics, clinical characteristics, disease duration and activity, comorbidities, and treatments were analyzed.ResultsData of 231 rheumatoid arthritis patients (84.8% female, median age, 56 years) were included; 153 were initially prescribed combination therapy and continued to their therapies; 31 were initially prescribed combination therapy but switched to monotherapy on their own volition (UM); 21 were initially prescribed monotherapy and switched to combination therapy; 26 were initially prescribed monotherapy and continued to their therapies. The rate of comorbidities at the time of data retrieval was higher in the UM group than in the combination group (83.3% vs. 60.3%, p = 0.031). Presence of comorbidities was a significant factor affecting switching to monotherapy (p = 0.039; odds ratio, 3.29; 95% confidence interval, 1.06-10.18). The combination and UM groups did not differ regarding remission rate assessed by Disease Activity Score 28-joint count C-reactive protein (60.5% and 70%, respectively; p = 0.328). Drug survival rates of the UM and combination groups did not differ. The median drug survival duration of tofacitinib was 27+ months with 1- and 4-year drug survival rates of 89.6% and 60.2%, respectively, in the UM group.ConclusionsAlthough 13.4% of the study population started monotherapy unintentionally, drug survival and remission rates of the UM and combination groups were not different. Comorbidity was a factor affecting transition from combination therapy to monotherapy.
Keywords: adherence; monotherapy; rheumatoid arthritis; survival; tofacitinib